Determinants of hospital patient safety culture - Montalbo-Montojo, Joan Grace (Manila: College of Nursing, University of the Philippines Manila, 2015)
The provision of healthcare is complex, and the risk that patients may be harmed while receiving care can never be mitigated entirely. In relation to this, health care organizations become aware of the importance of safety culture assessment and there is a widespread interest in measuring healthcare provider attitudes and perception about issues relevant to patient safety. The current study utilized a modified Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire to assess the patient safety culture of staff nurses working in government and private hospitals in Lipa City, Batangas. A descriptive, correlational and comparative design was selected for this study. Participants consist of two hundred forty three staff nurses from those meeting the inclusion criteria, available during data collection period and working in the above mentioned settings. -- The safety culture dimension that received the highest positive safety culture perception is teamwork while staffing received the lowest positive response. Significant differences were identified when it comes to teamwork, hospital handoffs and transitions, overall perceptions on safety, patient safety grade and number of events reported. Results also showed that the length of hospital experience is a significant predictor of supervisor/management expectations and staffing. The result of the study show that in general, the respondents have a positive regard toward patient safety culture within their organization. However, investing in practices and strategies that will further provide insight into nurses’ safety culture can be useful in raising safety awareness throughout the organization and will also identify areas needing improvement. Further research is also needed to identify other socio-demographic factors that can be predictors of patient safety culture.
Thesis (Master of Arts in Nursing - Adult Health Nursing) -- University of the Philippines Manila, June 2015.
Bibliography: leaves 106-115.
Keywords: Hospital patient safety culture